The baptism of the Christian adult: theme and variations - Burnish, Raymond (1983)
The thesis compares the teaching about Baptism contained in the catechetical and mystagogical teaching of the fourth century Churches in Jerusalem, Antioch and Mopsuestia with that of the period 1960-1980 emanating from the Church of South India and the Catholic, Orthodox and Baptist Churches in Britain. It considers the different approaches to catechesis and mystagogy of Cyril of Jerusalem, John Chrysostom of Antioch, and Theodore of Mopsuestia, and indicates the emphasis of Cyril on the necessity for the sincerity of the candidate, the pastoral concern and realism of John Chrysostom, and the emphasis on baptism as the symbol of the future which derives from Theodore. It also notes the differences in the situations and audiences for the material considered which is: the Procatechesis, Catecheses, and Mystagogical Catecheses of Cyril, the Catechetical Instructions of John Chrysostom, and the two works on the Faith and the Sacraments of Theodore. In the context of printed rather than oral instruction, a variety of modern works and liturgies are compared to give a composite view of each Church, although catechesis and mystagogy have tended to merge into one area of instruction. This modern material indicates a reversion to the earlier 'golden age of catechesis' of the fourth century, which in some situations is a conscious reversion, and in the others is an unconscious reversion to the fourth century due to the limited number of ways in which the baptismal rite can be explained. The link between baptism and ecclesiology is illustrated, as is the renewed importance of the community of the faithful in the acceptance and nurture of the candidates, and the renewal of interest in the role of the sponsor as the link between the candidate and the community.